Phytoremediation of Lead Polluted Soil by Glycine max L. - Sesan Abiodun Aransiola; Udeme Joshua Josiah Ijah; Olabisi Peter Abioye (Applied and Environmental Soil Science)
A study was designed to assess the phytoextraction potential of Glycine max L. for lead (Pb). Pots experiment was conducted. Viable seeds were planted in 5 kg of soil placed in each plastic pot having 0 ppm (control), 5 ppm, 10 ppm, 15 ppm, 20 ppm and 25 ppm of Pb respectively. The study was carried out for a period of 12 weeks under natural conditions. Physicochemical properties of the soil were determined using standard methods. The results revealed that pH, phosphorous and moisture contents increased while nitrogen and organic carbon contents decreased in polluted soil remediated with Glycine max L. compared to the unpolluted soil. Leaf, stem, seeds and roots of the plant were analyzed for Pb uptake after 12 weeks. The plants mopped up substantial concentration of Pb in the above plant biomass of the seeds (4.2 mg/kg), stem (1.37 mg/kg) and leaves (3.37 mg/kg) compared to concentrations in the roots (1.53 mg/kg). The phytoextraction ability of the plant was assessed in terms of its bioconcentration factor (BCF) and translocation factor (TF). It was observed that the levels of Pb in the roots and shoots after 12 weeks showed that more bioavailable pool of Pb was translocated from the root to seeds, leaves and stem in that order. The results obtained suggest that the plant has phytoextraction ability and could be used in restoring soil polluted with Pb.